Assisting decision-making on age of neutering for German Short/Wirehaired Pointer, Mastiff, Newfoundland, Rhodesian Ridgeback, Siberian Husky: associated joint disorders, cancers, and urinary incontinence - Hart, Lynette Arnason; Thigpen, Abigail Paige; Hart, Benjamin L.; Willits, Neil H.; Lee, Maya; Babchuk, Miya M.; Lee, Jenna; Ho, Megan; Clarkson, Sara T.; Chou, Juliann W. (Frontiers in Veterinary Science, 2024)
Spaying female and castrating male dogs, hereinafter referred to as neutering, became a U.S. convention for dogs' first year. Research on 35 breeds of dogs revealed that early neutering increases risks for some breeds of joint disorders---hip dysplasia (HD), elbow dysplasia (ED), or cranial cruciate ligament (CCL) tear---or cancers---lymphosarcoma (LSA), mast cell tumor (MCT), hemangiosarcoma (HSA), or osteosarcoma (OSA). Joint disorder risks are heightened for some larger breeds and for mixed breed dogs weighing more than 20 kg. Some breeds had elevated risks for cancers. Several other research teams have reported health complications associated with neutering. The study goal including using the same methodology for data collection and analyses as the 35 breeds paper for five additional dog breeds weighing at least 20 kg. The breeds were: German Short/Wirehaired Pointer, Mastiff, Newfoundland, Rhodesian Ridgeback, and Siberian Husky. Major differences among breeds appeared in vulnerability to joint disorders and cancers with early neutering: Pointer males and females had elevated joint disorders and increased cancers; Mastiff males had increased CCL and LSA and females had non-significant elevated CCL risks; Newfoundland females had heightened risks for joint disorders and males had non-significant elevated risks; Ridgeback females had heightened MCT with very early neutering; and Siberian Huskies showed no significant effects on joint disorders or cancers but females showed a non-significant but elevated CCL. Updated guidelines cover 40 dog breeds. These results further emphasize the importance of personalized decisions regarding neutering of dogs, considering the dog's breed, sex, and context